China’s Pledge to Civilise “All Under Heaven” - Klaas Dykmann (SAGE Publishing, 2021)
With China’s global rise, both its state leadership and key academics have engaged in developing a civilisational discourse for the twenty-first century partly based on ancient cosmological concepts. This article explores the meanings of and intentions behind this discourse, including its promise of a Chinese-led world order, and discusses its intended audience and international appeal. In the backdrop of theoretical debates on empires and their missions, the article claims that without a corresponding cultural appeal, China’s rising economic power and geostrategic clout are insufficient conditions to realise an empire in the classical sense. Growing inconsistencies mar the country’s imperial ambitions, such as those between a global civilising outreach and a toughening domestic embrace. Instead, imperial rhetoric is cautiously integrated in the party-state’s restoration of a Chinese “empire within,” indicating self-centredness and a lurking re-traditionalising of Chinese state power.